Preserved central nervous system functioning after use of romidepsin as a latency-reversing agent in an HIV cure strategy. (1st March 2022) - Muñoz-Moreno, Jose A.; Carrillo-Molina, Sara; Martínez-Zalacaín, Ignacio; Miranda, Cristina; Manzardo, Christian; Coll, Pep; Meulbroek, Michael; Hanke, Tomáš; Garolera, Maite; Miró, Josep M.; Brander, Christian; Clotet, Bonaventura; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To assess the central nervous system (CNS) impact of a kick&kill HIV cure strategy using therapeutic vaccine MVA.HIVconsv and the histone deacetylase inhibitor (HDACi) romidepsin (RMD) as latency-reversing agent. Design: Neurological observational substudy of the BCN02 trial (NCT02616874), a proof-of-concept, open-label, single-arm, phase I clinical trial testing the safety and immunogenicity of the MVA.HIVconsv vaccine and RMD in early-treated HIV-1-infected individuals. A monitored antiretroviral pause (MAP) was performed, with cART resumption after 2 pVL more than 2000 copies/ml. Reinitiated participants were followed for 24 weeks. Methods: Substudy participation was offered to all BCN02 participants ( N  = 15). Evaluations covered cognitive, functional, and brain imaging outcomes, performed before RMD administration (pre-RMD), after three RMD infusions (post-RMD), and at the end of the study (EoS). A group of early-treated HIV-1-infected individuals with matched clinical characteristics was additionally recruited ( n  = 10). Primary endpoint was change in a global cognitive score (NPZ-6). Results: Eleven participants from BCN02 trial were enrolled. No significant changes were observed in cognitive, functional, or brain imaging outcomes from pre-RMD to post-RMD. No relevant alterations were detected from pre-RMD to EoS either. Scores at EoS were similar in participants off cART for 32 weeks ( n  = 3) and those who resumed therapy for 24 weeks ( n  = 7). Controls showed comparable punctuations in NPZ-6 across all timepoints. Conclusion: No detrimental effects on cognitive status, functional outcomes, or brain imaging parameters were observed after using the HDACi RMD as latency-reversing agent with the MVA.HIVconsv vaccine in early-treated HIV-1-infected individuals. CNS safety was also confirmed after completion of the MAP.